Detection of neuroendocrine liver metastases with MnDPDP-enhanced MRI. - Rockall, A; Planche, K; Power, N; Nowosinska, E; Monson, J; Grossman, AB; Reznek, R (2009)
PURPOSE: The sensitivity of computerised tomography (CT) in detecting neuroendocrine liver metastases is variable and three-phase imaging is advocated. However, patients are often young and may require prolonged follow-up, thus a technique that avoids radiation exposure would be desirable. Our purpose was to assess the diagnostic performance of MRI, before and after administration of mangafodipir trisodium (MnDPDP), in the detection of neuroendocrine liver metastases. METHODS: Patients who had undergone single-phase or multi-phase contrast-enhanced MD-CT for neuroendocrine liver metastases were invited to have MRI. Two independent observers made quantitative measurements (number and size of lesions). All measurements were made on each available CT phase and all MRI sequences independently, and repeated after an interval to assess reproducibility. The final number of lesions was agreed on by consensus of three observers. A qualitative assessment (contrast and spatial resolution) and preferred modality were agreed on by consensus. RESULTS: 265 lesions were detected by consensus in 11 patients. Non-contrast CT was available in 4/11, arterial phase in 6/11 and portal phase in 10/11 patients. When compared with the consensus number of lesions, MD-CT identified 17% on non-contrast, 44% on arterial and 43% on portal venous imaging. Lesion detection on MRI was 48% on T(1)W, 52% on T(2)W and 92% on MnDPDP-MRI. The number of lesions detected on MnDPDP-MRI was closest to the final consensus reading (variance = 0.994, p = 0.0027). The reproducibility of lesion size measurements was best on MnDPDP-MRI (variance = 0.033, p = 0.0021). The preferred modality subjectively was MnDPDP-MRI in 9/11 cases and T(2)W MRI in 2/11. CONCLUSION: MRI is a robust technique in the demonstration of neuroendocrine liver metastases. It is highly reproducible in both detecting the number and measuring the size of lesions. We recommend T(2)W MRI and MnDPDP-MRI in detection and follow-up of neuroendocrine liver metastases.